Pengembangan Sistem Informasi Distribusi Produk Dengan Menggunakan Rational Unified Process (Studi Kasus Pada CV. Chiara Muslimah) - Randy Pramono Rahadian; Djoko Pramono; Adam Hendra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
CV. Chiara Muslimah is one of the Muslim fashion distributors in the city of Mojokerto. CV. Chiara Muslimah has become a distributor of many well-known brands, Seply, Elif, Ethica and others. Besides that, CV. Chiara Muslimah also has many members spread across various cities. Based on interviews, 83% of employees who work every day have the task of managing WhatsApp messaging group communications respectively. As well as employees can only serve customer requests only during business hours, as a result customer questions are not answered and orders are not received. Based on these problems, a solution can be given, namely an information distribution system. The method used in development is the Rational Unified Process, the method was chosen because there is an analysis of business processes in one phase and complete in the documentation. The results of this study produced 13 sequence diagrams, 2 class diagrams, and 1 physical data model. From the results of testing the black box the results are 100% valid. Based on UAT testing which contained 18 questionnaires, it was obtained an examination of 86.51%. And a comparison of the business process of question and answer as much as 5 minutes and accelerate business processes as much as 8 minutes 27 seconds.